Effect of (+)-cyanidanol-3 on chronic active hepatitis: a double blind controlled trial. Issue 9 (September 1985) - Bar-Meir, S; Halpern, Z; Gutman, M; Shpirer, Z; Baratz, M; Bass, D
Abstract : Forty patients with biopsy proven chronic active hepatitis were studied, 22 received (+)-cyanidanol-3 in a dose of 3 g daily and 18 placebo. Side effects related to cyanidanol were fever (four patients), haemolysis (one patient) and urticaria (one patient). All side effects subsided on discontinuation of the medication. Cyanidanol had an effect no better than placebo on symptoms, laboratory tests, and histological findings on liver biopsy.